Reducing Eleventh-Grade Students' Misconceptions on Gravity Concept using PDEODE*E-Based Conceptual Change Model - Zulfikar, A.; Saepuzaman, D.; Novia, H.; Setyadin, A. H.; Jubaedah, D. S.; Sholihat, F. N.; Muhaemin, M. H.; Afif, N. F.; Fratiwi, N. J.; Bhakti, S. S.; Amalia, S. A.; Hidayat, S. R.; et al. (IOP PUBLISHING LTD, 2019)
Students' misconceptions as one of learning problems that able to inhibit their learning achievement. One of the fundamental subjects in the physics learning is the force concept, such as gravity. This study was conducted to reduce students' misconceptions on gravity concept through Predict-Discuss-Explore-Observe-Discuss-Explore*-Explain-based PDEODE*E-based Conceptual Change Model (PDEODE* E-based CCM). The gravity concept in this study is on the falling ball in several different cases. The participants of this study consisted of 33 eleventh-grade students of Senior High School in Bandung. The students' misconception was detected using Four Tier Test-formatted Force Concept Inventory (4TT-FCI) as the diagnostic instrument test. The result of this study shows that students' misconception on gravity had been reduced from 56.82% to 15,91% after using PDEODE*E-based CCM in the learning process. It can be concluded that the utilizing of PDEODE*E-based CCM is able to reduce students' misconception on gravity concepts.
Keywords: TEACHERS MISCONCEPTIONS; Physics